PRZEŻYWANIE STAROŚCI PRZEZ SAMOTNE KOBIETY W ZALEŻNOŚCI OD MIEJSCA ZAMIESZKANIA - Pilch, Tadeusz; Zielińska, Iwona (Wydział Prawa i Administracji UAM, 1999)
In 1998 sixty women have been the object of a research study; they were aged from 60 up to 95 years. Twenty of them lived in blocks of buildings, other twenty - in a home for the aged and the last twenty - with their families. The criterion of a „successful life” is very much individualised in the eyes of the elderly. One could say that it has poor number of external indications, but it has one main determinant: internal, deeply subjective conviction. As to external criteria - they are mostly a degree and a form of wealth, next - interpersonal relations as well as the attributes and attitudes in relation with morality and religion. The women examined do belong to the generation whose youth and maturity were the period of the biggest poverty and privation; this is why their material aspirations and a horizon of wishes have always been extremely modest: mere and ordinary satisfaction of everyday needs. Loneliness was commonly considered to be particularly painful form of a „failed, unsuccessful life”. That is why most complaints because of such a failure were heard by the Authors from the women living in a home for the aged.
LIVING THROUGH OF THE OLD AGE BY LONELY WOMEN DEPENDING ON THEIR PERMANENT RESIDENCE PLACE